Ricardo Palma y Simón Bolívar a propósito del dictador Francia, del Paraguay - Ayala Olazával, José Luis (2018)
The language and lexicon of the liberator Simón Bolívar were collected by Ricardo Palma in several of his traditions. Nevertheless, there is a veil of mystery about the originality of some words and phrases attributed to the Venezuelan general. In this sense, the present work offers us some ideas on this subject.